PERENCANAAN PENGEMBANGAN SEKTOR PERTANIAN SUB SEKTOR TANAMAN PANGAN DI KABUPATEN KULONPROGO - Fafurida, - (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The objective of this research is to make planning in the development of agricultural sector especiallyfood crops for the economic area improvement. The tools of analysis applied are shift share, LocationQuotient (LQ) and central index analysis. The development of the superb food crops is conducted withthe development of processing and central industry. By observing the superb crops commodity, centralindex value, and PRDB per capita, it can be determined the development direction of each food cropscommodities, that is by specifying central production area and processing industry. Paddy centralproduction is recommended in Temon, Panjatan, Galur, Lendah, Kokap, Girimulyo, Nanggulan andSamigaluh sub-districts, and rice mill is developed in Wates and Pengasih sub-districts. For Maizecommodity, the development of processing industry is conducted in Sentolo and Pengasih sub-districtsand its central production is in Temon, Lendah, Kokap, Kalibawang and Samigaluh sub-districts. Forcassava crops commodity, the central production is in Temon, Kokap, Girimulyo, Kalibawang andSamigaluh sub-districts, and its processing industry is founded in Sentolo and Pengasih sub-districts.Central production of sweet potatoes is in Panjatan, Pengasih, and Girimulyo subdistricts, and itsprocessing industry is in Wates sub-district. For peanuts commodity, the processing industry is foundedin Wates and Pengasih sub-districts, and its central production is in Temon, Lendah, Kokap, Girimulyoand Samigaluh sub-districts. Central production of soybeans crops commodity is located in Temon,Galur, Lendah, Nanggulan and Kalibawang sub-districts and its processing industry is in Sentolo andPengasih sub-districts. Temon, Sentolo, and Pengasih sub-districts are the central production for thegreen beans crops with processing industry in Wates sub-district.Keywords: development, food crops, superb commodity